Potensi Lahan Untuk Tanaman Kelapa (Cocos nucifera L) Di Kecamatan Wori Kabupaten Minahasa Utara - Sari Prativi Suratinojo; Joice Supit,; Yani Kamagi; Meldi Sinolungan (COCOS, 2013)
AbstractWori districts which has an area of 90.704 km2 is one of North Minahasa district that processed into oil palm plantations, coconut flour, nata de coco, coconut shell charcoal and coconut trees. Coconut flour is one of the oil derivative products (integrated coconut) recorded the many buyers and scattered in almost all parts of the world. Buyers of coconut flour was more focused on Eastern Europe, but is now rapidly spreading evenly over all the continents in the world. Anticipate in terms of availability of coconut flour it is necessary to the development of the coconut crop, given the current availability of old coconuts began to decrease. This study aims to determine the potential of land for coconut (Cocos nucifera L) in District Wori North Minahasa regency. This research can provide input and information to the government and the people of North Minahasa district Wori in coconut planting efforts. The research was conducted in the District of North Minahasa regency Wori, and in Laboratory Soil Department of Faculty of Agriculture, University of Sam Ratulangi Manado. This study was conducted in July 2009 and September 2011. Research methods implemented by way of a survey method with land unit approach, the observed variable is the slope, effective depth, texture, erosion, drainage, soil type and land use. The data were then arranged in tabular form later described descriptive to determine appropriate land or potentially and inappropriate or potentially for coconut by coconut trees growing conditions The results showed that in the region have Wori climate types B1, namely: 7-9 wet months and <2 dry months. Wori altitude region is 0-610 meters above sea level with the form region is rather flat, undulating to mountainous. Slopes in the study area is dominated by slopes <15%. Wori soil characteristics in the area, where the physical and chemical properties of the soil, namely: effective depth, texture and drainage and soil pH, indicating that the soil in the area has the potential to Wori Based on comparison of coconut and palm trees growing conditions with the conditions of the study area Wori region potential for development of coconut plantations with a total area of 4637.80 ha